Mapeamento urbanístico: a materialidade da dimensão intangível do patrimônio cultural urbano - Ana Cecilia Nascimento Rocha (2005)
The concept of heritage, as well as culture, hás been enlarged, starting new questions about the preservation and comprehension. Currently the term culture heritage goes far the original sense of material goods. It also has now a collective foundation and an untouchably substrate: the denominated immaterial or intangible cultural heritage, that includes the oral traditions, habits, languages, music, celebrations, rituals, traditional medicine, gastronomy and all specials skills related with the material aspects of culture, for example the tools and the spaces where these activities take place denominated cultural spaces, support of tradition. Every material testimony has an intangible dimension; as the same way, each immaterial heritage possess a tactile dimension, reveling itself by the materiality, by the hand that elaborate the arts, by the space where the activities take place, by the nature appropriated and modified, by the objects that compound the practice. In the last item of its specifics goal, the INRC (National Inventory of Cultural References, produced by the federal department of cultural heritage in Brazil IPHAN), identifies the Architecture and the Antropology as being the most important disciplines dedicated to the heritage theme. Thus, based on INRC and the study of the Places Cultural Register, we intend to achieve three principal objectives in this research: 1) To congregate, in various areas of knowledge, the methodologies, information and technologies that could be applied in the urban mapping of cultural spaces; 2) To develop and integrate these methodologies to elaborate a unified, panoramic and clear final product; 3) To evidence, with a study case at the Bernardo Monteiro Avenue Cultural Space, in Belo Horizonte city, the importance of the architect contribution in registration, protection and investigation of the intangible urban heritage, by the mapping and analyses of its material dimension. Beyond the conventional resources of mapping, advanced technologies in laser scanning of facades and urban places were successfully tested. Lastly, we have enumerated some propositions of continuity to this research that, because of the complexity and magnitude of the object the city itself and its cultural heritage demands continous and dedicated investigation.